The Impact Of Making Organizational Sense On Lean Management : A Descriptive Analytical Research In The Iraqi Ministry Of Education - Daham Khalaf, Abd-al hakeem; Abd- alqadeer Ahmed Al- Nuiami, Salah (Journal of Economics and Administrative Sciences, 2024)
The idea of ​​organizational sense industry involves how members of organizations reach to understandings about the environment through different behaviors, and how these understandings represent the basis for the nature of subsequent reactions. The organizational sense industry variable represents the independent variable. The lean management approach has become a comprehensive thought applied in all fields and business activities. In order to achieve the best performance through the best outputs. The research aims to highlight the level of general awareness of the educational administrations regarding the nature of the sense making in the institution of the Iraqi educational sector. The research problem is what is the impact level of organizational sense making on solidifying lean management practices in the Iraqi Ministry of Education? The descriptive analytical approach was used to describe and analyze the main research variables. The research sample consisted of 215 participants in middle and top administrative leaders in the education directorates of the Ministry of Education. A group of statistical methods are used, which are the (Amos.V25) program, and the (SPSS) program. Findings revealed the existence of a weakness in the overall base of organizational cultures for the ministry's education directorates in defining the criteria for understanding what is agreed upon or disagreed upon related to the nature of formal and informal behavior in different performance approaches.                                                             Paper type: Research paper.